Assessment of cardiovascular risk factors in people with HIV infection treated with ART in rural South Africa: a cross sectional study - Felistas Mashinya; Marianne Alberts; Jean‐Pierre Van Geertruyden; Robert Colebunders (2015)
The risk of cardiovascular diseases (CVD) in human immunodeficiency virus (HIV) infected people on antiretroviral therapy (ART) from some rural parts of Africa is not well known. We assessed CVD risk factors, the estimated 5-year Data collection on adverse effects of anti-HIV drugs (DA.) risk score and the 10-year Framingham risk score in persons with HIV infection on ART in a rural area in South Africa. A cross-sectional study in which the data on demographic, lifestyle, and chronic disease were collected using the World Health Organization Stepwise approach to surveillance questionnaire. Biochemical parameters were tested using standard biochemical methods. CD4 counts were performed using PIMA analyser and viral load was tested using the branched deoxyribonucleic acid technique. Student t test and Chi square test were used on continuous and categorical variables respectively. Bivariate and multivariate logistic regression were used to analyze predictors of CVD risk factors. Estimates of 5 and 10-year CVD risk were calculated using online tools. The Cohen's kappa coefficient was used to assess the agreement between CVD risk equations. The mean age of participants was 44.8 ± 11.8 years; 79.9 % were females. Most of the participants (85 %) had an undetectable viral load and a mean CD4 count of 462 ± 235 cell/mm3. The most common CVD risk factors were low high density lipoprotein cholesterol (HDL-C) (43.8 %), hypercholesterolaemia (33.2 %) and a high Apolipoprotein (Apo) B/ApoA ratio (45.4 %).Using the Framingham equation, 6.7 % of participants had a moderate to high 10-year CVD risk while the DAD risk equation showed that 31.1 % of participants had a moderate to high 5-year CVD risk. Most participants had a low CVD risk by both risk equations. The level of agreement between the two risk equations was 73.8 % (k = 0.23; 95 % CI 0.10–0.35; p value 0.001). CVD risk factors were common among this rural population on ART. The high proportion of participants with a moderate to high CVD risk, observed with the DAD risk equation, clearly represents a considerable health burden that can possibly be reduced by increasing educational programs on CVD prevention for people on ART. There is however a need to develop and evaluate a race/ethnicity-specific CVD risk estimation tool for HIV infected Africans.